2012
DOI: 10.1007/s00394-012-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of almonds on inflammation and oxidative stress in Chinese patients with type 2 diabetes mellitus: a randomized crossover controlled feeding trial

Abstract: Our results suggested that incorporation of almonds into a healthy diet could ameliorate inflammation and oxidative stress in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 45 publications
7
77
1
2
Order By: Relevance
“…Jiang et al [39] noted in the Multi-Ethnic Study of Atherosclerosis that inflammatory biomarkers were inversely associated with an increased frequency of nut and seed consumption. Consistent with this observational data, we previously found that almonds decreased IL-6 and CRP, and TNF-α in Chinese patients with type 2 diabetes but did not affect ICAM-1 or VCAM-1 [40]. Rajaram et al [41] also reported that almond intake diminished CRP in free-living healthy adults although no dose–response relationship was noted.…”
Section: Discussionsupporting
confidence: 79%
“…Jiang et al [39] noted in the Multi-Ethnic Study of Atherosclerosis that inflammatory biomarkers were inversely associated with an increased frequency of nut and seed consumption. Consistent with this observational data, we previously found that almonds decreased IL-6 and CRP, and TNF-α in Chinese patients with type 2 diabetes but did not affect ICAM-1 or VCAM-1 [40]. Rajaram et al [41] also reported that almond intake diminished CRP in free-living healthy adults although no dose–response relationship was noted.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, in a sample of adults with pre-diabetes, pistachio consumption for 4 months did not affect circulating measures of inflammation but did reduce lymphocyte gene expression of interleukin-6 [27], suggesting that pistachios may have a nominal effect on inflammation that was not detected in previous work. We found no effect on any markers of inflammation in the present study; however, we did not assess interleukin-6, which has been reduced by pistachios in the above-mentioned study [37], and also by almonds in another study of type 2 diabetes [17]. The variability among studies in participant demographics, type of nut(s) consumed, and markers of inflammation evaluated makes it difficult to draw conclusions about the role of nuts in inflammation.…”
Section: Discussioncontrasting
confidence: 57%
“…A few trials reported beneficial effects on the lipid/lipoprotein profile [1115], and a recent meta-analysis concluded that daily nut consumption reduces fasting glucose and glycated hemoglobin (HbA1c) [16]. Two studies that assessed inflammatory markers following nut interventions reported mixed results [17, 18], and one study reported a significant improvement in endothelial function following 8 weeks of walnut consumption [14]. However, most trials (regardless of the population) have studied mixed nuts or walnuts, and the health benefits of other nuts, such as pistachios, are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is possible that a high intake of nuts may reduce the severity of disease and progression to death as indicated by studies which found that patients with diabetes, coronary heart disease, and heart failure who consumed more nuts had a reduced risk of cardiovascular disease or all-cause mortality [8183]. Although we observed similar associations for both incidence and mortality from coronary heart disease and cardiovascular disease, epidemiological studies on nut consumption and type 2 diabetes incidence have largely shown no association [29], while in the present meta-analysis we found a reduced risk of diabetes mortality, which might be due to reduced risk of cardio-metabolic risk factors and complications in diabetes patients with a high nut intake [8385]. …”
Section: Discussionsupporting
confidence: 52%